IoT based climate smart agriculture succeeded by blockchain database—A bibliometric analysis - Safeer, Sajid; Mastro, Giuseppe De; Pulvento, Cataldo (Frontiers in Sustainable Food Systems, 2024)
Modern-day agriculture is vital for sustainable production, ensuring a consistent supply of food and fiber for humanity. The data proving its quality is economically significant, encompassing farm conditions, irrigation practices, inventories, contracts, and deals within the agro-food supply sector. To ensure transparent and secure data transfer and storage, a trustworthy interconnected databank is essential for all concerned authorities and contributors. The integration of Internet of Things (IoT) in agriculture with blockchain technology offers an unparalleled solution. This combination serves as a distributed ledger, ensuring transparent and secure management of critical environmental and supply chain data. The IoT-based blockchain infrastructure enhances agricultural sustainability and environmental monitoring. It is anticipated that this technology will become increasingly accurate and effective in addressing persistent challenges in the agro-food sector. This bibliometric analysis reviews and synthesizes relevant literature from the Scopus database, highlighting the growth and trends in IoT and blockchain research applied to precision agriculture. The study reveals a remarkable 47.58% annual growth rate in research within this field, starting with only three published documents in 2019 and peaking at 21 in 2022 and 20 in 2024. Globally, China and India lead in publication output, collectively accounting for 62% of the articles. In terms of citations, India ranks highest with 550 total citations, followed by Italy with 431 citations during 2019–2024. This comprehensive study serves as a valuable reference for understanding the research trends and growth in IoT and blockchain applications in agriculture, providing critical insights for future developments in this rapidly evolving field.